2016
DOI: 10.1007/s11144-016-1123-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous catalytic Wacker oxidation of ethylene over oxide-supported Pd/VOx catalysts: the support effect

Abstract: from the reacting system. In absence of any of the components no selective catalytic partial EE oxidation proceeded, indicating that the Wacker mechanism could not operate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Better isolation of products can be achieved by preparing the catalysts on different supports including palladium-and copper-exchanged zeolites [8][9][10][11][12][13][14][15] , palladium clusters on titania 16 , and palladium on carbon nanotubes 17 . Other chloride-free systems have been proposed, such as palladium deposited on vanadium pentoxide [18][19][20] , palladium on vanadia nanotubes 21 and palladium and manganese salts of heteropoly acids on silica 22 with different co-catalysts replacing the Cu(II)/Cu(I) redox couple. However, most of these catalyst systems either lacked sufficient activity or stability.…”
mentioning
confidence: 99%
“…Better isolation of products can be achieved by preparing the catalysts on different supports including palladium-and copper-exchanged zeolites [8][9][10][11][12][13][14][15] , palladium clusters on titania 16 , and palladium on carbon nanotubes 17 . Other chloride-free systems have been proposed, such as palladium deposited on vanadium pentoxide [18][19][20] , palladium on vanadia nanotubes 21 and palladium and manganese salts of heteropoly acids on silica 22 with different co-catalysts replacing the Cu(II)/Cu(I) redox couple. However, most of these catalyst systems either lacked sufficient activity or stability.…”
mentioning
confidence: 99%
“…[58][59][60] Many reports have revealed that Pd doped V 2 O 5 supported on TiO 2 exhibited high catalytic activity in the vapor-phase conversion of ethylene. 36,61,62 The V 2 O 5 in the Pd-V 2 O 5 system enabled the facile re-oxidation of Pd 2+ to Pd 0 . To conrm the reducibility of the catalysts in this study, H 2 -TPR measurements were performed on the V 2 O 5 -TiO 2 and 2Pd-V 2 O 5 -TiO 2 catalysts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In propene epoxidation, water suppresses the deactivation of gold–titania while slightly diminishing the overall activity . For Wacker oxidation, water oxidizes ethylene to acetaldehyde based on isotope incorporation experiments from previous studies on both homogeneous and heterogeneous systems. In the homogeneous Wacker system, water is used in excess as a solvent, rendering kinetic and mechanistic studies involving water challenging. The exact role of water in the heterogeneous Wacker process has not been established.…”
Section: Introductionmentioning
confidence: 99%